Public Relations Strategy of the Secretariat of DPRD West Sumatra Province in Creating Instagram Content for Public Information Dissemination - Rindiyani, Nurannisa (AMK : Abdi Masyarakat UIKA, 2025)
In the digital era, social media has become an essential tool for government institutions to effectively disseminate public information. The Secretariat of the West Sumatra Provincial Parliament (DPRD) utilizes Instagram as a communication channel with the public. However, challenges in managing Instagram content require an appropriate public relations (PR) strategy to ensure that the information shared is not only informative but also engaging and capable of reaching a broader audience. This study analyzes the PR strategy of the DPRD Secretariat in creating Instagram content using a qualitative approach through observation and literature review. The findings indicate that the success of this strategy depends on visual quality, public interaction, utilization of Instagram features, and consistency in publication. However, challenges such as low engagement and minimal responses to public comments remain obstacles that need to be addressed through content innovation and improved interaction management.